„Инастрики” и „тундрюки” в современном русском сленге: деривационный и стилистический аспекты сленговых номинаций иностранцев и провинциалов - Chabibullina, Elena (Studia Rossica Posnaniensia, 2010)
This paper deals with the slang derivations of the modern Russian language, related to the notions of “иностранец”, “инородец”, “провинциал”, “провинция”. Key aspects of the analysis of these language units are the aspects of word formation and the Russian language, due to the permanent extralinguistic factors, there is a large number of expressive ethnonyms.The area of their distribution is the sphere of the various social dialects, hence they get into general use (for example, in colloquial language). Our task is to identify how the derivational features of these formations determine their emotional and expressive color.